Studying the Implementation of Potentiometric Methods for the Detection of Cracks in Renovation of Forging Tools - Jozef Pilc; Michal Derbas; Miroslav Janota; Mario Kosut (Communications - Scientific letters of the University of Zilina, 2014)
Mass production using forging tools leads to an enormous increase in the consumption of forging tools and the need for rapid and flexible tool renovations. A major shortcoming in the renovations is the failure to identify cracks propagating from the surface towards the core of the basic components. Forging tools made from special tool steels are highly cost-intensive. The main cost component is the price of the material, heat treatment and other chemical-heat treatment surfaces. This is the main reason why it is necessary to think about renovation at the design stage, in case of the need for repairs. An important factor in the renovation process is the optimal choice of technology to restore the mechanical and physical properties of tools at an acceptable price, of course. The main issue in the choice of the optimal technology is heat treatment to achieve a high hardness and surface of the die, which is nitrided to ensure wear resistance. This article deals with the application of non-destructive detection technology when considering the size of die forging defects that arise in the process of forming.